2008
DOI: 10.3163/1536-5050.96.2.101
|View full text |Cite
|
Sign up to set email alerts
|

Hispanics' use of Internet health information: an exploratory study

Abstract: This study provides further evidence of differences in Internet health information seeking among Hispanics and non-Hispanic whites. Cultural discordance may be a possible explanation for Hispanics' view that the Internet negatively impacts physician-patient relationships. Strategies to increase Hispanics' access to Internet health information will likely help them become empowered and educated consumers, potentially having a favorable impact on health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
73
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(82 citation statements)
references
References 0 publications
8
73
1
Order By: Relevance
“…However, these same approaches may not be reaching certain populations due to "digital divide" issues of differential access to the Internet and other computer technologies among different demographic groups [9][10]. Despite the importance of these issues, relatively few studies have reported on the reach of behavioral interventions in general [11] or of interactive behavior-change technologies more specifically [12].…”
Section: Introductionmentioning
confidence: 96%
“…However, these same approaches may not be reaching certain populations due to "digital divide" issues of differential access to the Internet and other computer technologies among different demographic groups [9][10]. Despite the importance of these issues, relatively few studies have reported on the reach of behavioral interventions in general [11] or of interactive behavior-change technologies more specifically [12].…”
Section: Introductionmentioning
confidence: 96%
“…Latinos, compared to non-Hispanic whites, tend to have less access to the Internet and tend to use the Internet less for seeking health information. 13,14 However, as in other ethnic groups, access to computers and the Internet is related to education and socio-economic class. Limited access to technology is certainly a factor, but so is a relative scarcity of programs designed for Spanish-dominant Latinos.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Latinos are less likely to have high computer use efficacy, have a lower online health system activation rate, and have less success in activating eHealth portals than NH Whites. [13] While some state and local level examinations of online HISB and the use of HIT exist, [7,[14][15][16][17] and several national level studies, [1,9] these studies do not control for other factors such as Latino sub-ethnicity or nativity that might be important cultural variables that could contribute to or mitigate disparities.…”
Section: Introductionmentioning
confidence: 99%